PANDANGAN ISLAM TERHADAP TRADISI PERNIKAHAN DALAM PROSESI UPACARA MANOE PUCOK - Fitriani; Fahmi Arfan; Irwan (Indonesian Journal of Islamic and Social Science, 2024)
His article aims to explain the Islamic view of the wedding tradition in the Manoe Pucok ceremony procession. This research is a field research, using an anthropological approach. In this study, researchers used qualitative data analysis techniques with descriptive methods. Based on the results of this study, it shows that the Islamic view of the marriage tradition in the Manoe Pucok ceremony if it is carried out in an appropriate manner and does not conflict with sharia law, the teachings of Islam allow it. The values contained in the implementation of this tradition are an expression that symbolizes self-cleansing before starting a new life. Manoe Pucok is an event that bathes the bride and groom the day before the wedding. Therefore, Manoe Pucok has become a culture for the people of Aceh as it is today. A wise saying in the maja hadith states "Mate aneuk meupat jeurat, gadoeh adat pat tamita", the meaning of these words is: if a child dies, know where the grave is.